PEMAHAMAN KONSEP MATEMATIKA: KOMPARASI PEMBELAJARAN MATEMATIKA REALISTIK DAN METODE KONVENSIONAL - Rangkuti, Hariman Hasayangan; Rangkuti, Ahmad Nizar; Amir, Almira (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The Realistic Mathematics Education approach emphasizes understanding concepts through the context of everyday life, while conventional methods can provide a solid foundation in mathematical concepts. Therefore, teachers use conventional and realistic methods in teaching mathematics to improve student learning outcomes. Comparative analysis is the research method used in this study. The purpose of the Comparative Study between Realistic Mathematics Learning and Conventional Methods in Improving Students' Understanding of Mathematics Concepts is to compare how well the two approaches, realistic mathematics learning and conventional methods, in improving students' understanding of mathematics concepts. This research aims to find out whether the conventional approach or the Realistic Mathematics learning method is more effective in helping students understand mathematical concepts. It is expected that the information or data obtained from this research can provide an overview of learning strategies that are more effective in improving students' understanding of mathematical concepts. The final result of this research is expected to provide important data related to learning strategies that are more feasible to help students in understanding numerical ideas. The results of this study will have a significant impact on the development of more efficient methods for teaching mathematics in the classroom.